2019
DOI: 10.9778/cmajo.20180148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comprehensive hospice palliative care on end-of-life care: a propensity-score–matched retrospective observational study

Abstract: F or patients with cancer facing terminal illness, a hospice palliative care approach is an important component of quality care and can offer many benefits to patients and their families, including pain and symptom management, coordination of care and improved quality of life. 1-4 In addition, a hospice palliative care approach offers substantial benefits to the health care system, including the decreased use of potentially aggressive end-of-life care, 4 which is costly 5-7 and is often not the wish of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Comparison with other studies Many studies have reported on the relationship between PC exposure and hospital-based acute care near the EOL in patients with cancer, [15][16][17][18][19][20][21] consistently finding that PC exposure reduces risk of hospital-based care near the EOL. Fewer studies have focused on patients without cancer, and results have been limited to the disease categories examined (heart failure, [36][37][38][39] dementia, 40 41 end-stage renal disease (ESRD), 42 43 and end-stage liver disease 44 ).…”
Section: Open Accessmentioning
confidence: 94%
See 1 more Smart Citation
“…Comparison with other studies Many studies have reported on the relationship between PC exposure and hospital-based acute care near the EOL in patients with cancer, [15][16][17][18][19][20][21] consistently finding that PC exposure reduces risk of hospital-based care near the EOL. Fewer studies have focused on patients without cancer, and results have been limited to the disease categories examined (heart failure, [36][37][38][39] dementia, 40 41 end-stage renal disease (ESRD), 42 43 and end-stage liver disease 44 ).…”
Section: Open Accessmentioning
confidence: 94%
“…Many studies have reported on the relationship between PC exposure and healthcare resource use near the EOL for patients with cancer, [15][16][17][18][19][20][21] consistently finding that PC exposure reduces risk of hospital-based care near the EOL. Recently, the same was found to be true for patients with many of the most common chronic diseases; however, questions remain about the role of PC timing on these outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Income is classified into five categories: 1 (lowest), 2, 3, 4, 5 (highest). The income quintiles were chosen based on recent peer reviewed literature using ICES data [48][49][50], and the importance of placing this work in the context of other studies in the field. Income quintile was only considered at the index date, and we did not account for patients moving between neighborhoods.…”
Section: Plos Onementioning
confidence: 99%
“…This is important, as this might be the only visual evidence of the patient's death and it is also cathartic for the NOK who were unable to visit or communicate with the patient prior to their passing. 4 Regarding funeral arrangements, a list of certified funeral companies who are able to comply with infection precautions should be provided. In Singapore, funerals are held with a windowless casket and are limited to a maximum of 3 days, with no more than 10 in attendance.…”
Section: Upon a Patient's Passingmentioning
confidence: 99%